Right coronary artery thrombosis within drug eluting stents more than 10 years after deployment: Two cases of very, very late stent thrombosis - Sam Lovibond; Michael Leung (Heart Vessels and Transplantation, 2017)
We present two rare cases of very late stent thrombosis occurring beyond ten years post initial drug eluting stent deployment.